Аналіз економічної ефективності діяльності мисливських господарств України - Прус, Юрій Олександрович; Prus, Yurii; Яворська, Тетяна Іванівна; Yavorska, Tetiana (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: Досліджено рівень економічної ефективності діяльності мисливських господарств України та аспекти його формування на сучасному етапі. Проведено аналіз натуральних та вартісних показників економічної ефективності діяльності мисливських господарств, таких як питома вага добутих мисливських тварин, кількість добутих мисливських тварин та вихід валової продукції на одиницю площі, продуктивність праці, окупність витрат, рівень витрат на охорону, відтворення та облік диких тварин,упорядкування мисливських угідь, чисельність поголів’я мисливських тварин у розплідниках і діловий вихід молодняка на одиницю площі. Встановлені відмінності у рівнях показників економічної ефективності мисливських господарств в залежності від природно-кліматичних умов. Обґрунтовано необхідність зміни структури мисливських угідь та підвищення щільності мисливських тварин. /// EN: Hunting in Ukraine remains unprofitable. During the analyzed period, the industry’s payback rate averaged 48.6%. Hunting income grew annually, but the growth rate was lower than the growth rate of costs. This situation is negative, as it indicates a low level of financing for the development of hunting. The main source of income for hunting is funds from the production of game animals. Their production volumes per 1 thousand ha and the specific weight of production have been decreasing for a long time, only ungulates have shown a slight increase in recent years. There are persistent differences in the production indicators of hunting animals in the natural and climatic zones of Ukraine, which are certainly reflected in the cost indicators of the efficiency of hunting farms. In 2010–2013, the lowest gross product yield per 1 thousand ha of hunting grounds and the lowest labor productivity were observed in Polissya, and the highest in the Forest-Steppe. However, from 2014 to 2017, production in Polesie increased by 81.4%, which is associated with an increase in ungulate output by 44.7%. Meanwhile, the Steppe saw a decrease in gross product production by 8.8%, and as a result, the Steppe hunting grounds became the least productive among the natural and climatic zones. To increase the level of payback, it is necessary to increase the output of gross product, which will depend on changes in the structure of hunting grounds, changes in the composition of hunting animals, and changes in the composition and level of costs. A change in the composition of hunting animals will affect the production volume. This can occur extensively (due to changes in the structure of hunting grounds) and intensively (due to an increase in the density of hunting animals). Both methods require several organizational, economic, and legal measures, particularly an increase in the breeding of hunting animals in nurseries. Additional methods of financial support for hunting farms can be training, competitions, rental, recreation, etc. Keeping wild animals in enclosures is also essential because it protects them from predators and poachers, increasing the species’ population and, as a result, income and profit.
Analysis of the economic efficiency of the activities of hunting farms in Ukraine
Keywords: аналіз; економічна ефективність; мисливські господарства; добуті мисливські тварини; вихід продукції; окупність витрат; analysis; economic efficiency; hunting farms; hunted game animals; product yield; cost recovery